A proposed strategy for employing the Nubian folklore in metal furniture design (an applied study) - Waleed Abdelfatah Afify (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
Nubian folk art is considered in all its forms an artistic production characterized by originality and innovation, full of symbols and linked to history and legend. Furniture design in general and metal furniture design in particular as the subject of research from The design fields that draw their design inspiration from multiple sources, and the Nubian folklore is one of the most important of those sources, which is characterized by being in the first place with its own character, which was influenced by the ancient Egyptian and Islamic architecture, which created a unique blend of design vocabulary bearing the fragrance of the past and the authenticity and identity of the present. The research came to the conclusion of a design strategy for metal furniture by employing the vocabulary of the Nubian folklore and achieving its formal values and symbolic connotations. Third: The strategy of employing the Nubian folklore in the design of metal furniture (an applied study). The research reached a design methodology that relies on the vocabulary of the Nubian folklore as an entrance to the design process by interacting with the symbolic connotations to achieve the design thought in terms of formality and functionality, where the resulting design alternatives developed by the designer can show multiple predictive solutions, and design forms that show themselves through Its own form and expressive of the Nubian folklore.